2017
DOI: 10.1002/prot.25385
|View full text |Cite
|
Sign up to set email alerts
|

Archaea S‐layer nanotube from a “black smoker” in complex with cyclo‐octasulfur (S8) rings

Abstract: Elemental sulfur exists primarily as an S80 ring and serves as terminal electron acceptor for a variety of sulfur-fermenting bacteria. Hyperthermophilic archaea from black smoker vents are an exciting research tool to advance our knowledge of sulfur respiration under extreme conditions. Here, we use a hybrid method approach to demonstrate that the proteinaceous cavities of the S-layer nanotube of the hyperthermophilic archaeon Staphylothermus marinus act as a storage reservoir for cyclo-octasulfur S8. Fully at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…All molecular dynamics simulations of RHCC − water complexes were based on a higher pressure structure PDB 1YBK which was crystallized at P = 15 atm and T = 273 K , and which contained clusters of 13 water molecules in cavity 2 and 8 water molecules in cavity 3. All simulations of the RHCC − cyclo − octasulfur complex were based on the structure PDB 5JR5 [ 11 ] which was crystallized at T = 277 K and which contained a single crown-shaped S 8 ring in cavity 2 with a geometry similar to crystalline α − S 8 and two competing equal-occupancy conformations in cavity 3, one similar to the twisted-ring S 8 arrangement and one in the exo − endo − S 8 arrangement. For both complexes, this investigation was focused exclusively on cavity 3 and its contents and the twisted-ring conformation of S 8 was selected for analysis.…”
Section: Systems and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All molecular dynamics simulations of RHCC − water complexes were based on a higher pressure structure PDB 1YBK which was crystallized at P = 15 atm and T = 273 K , and which contained clusters of 13 water molecules in cavity 2 and 8 water molecules in cavity 3. All simulations of the RHCC − cyclo − octasulfur complex were based on the structure PDB 5JR5 [ 11 ] which was crystallized at T = 277 K and which contained a single crown-shaped S 8 ring in cavity 2 with a geometry similar to crystalline α − S 8 and two competing equal-occupancy conformations in cavity 3, one similar to the twisted-ring S 8 arrangement and one in the exo − endo − S 8 arrangement. For both complexes, this investigation was focused exclusively on cavity 3 and its contents and the twisted-ring conformation of S 8 was selected for analysis.…”
Section: Systems and Methodsmentioning
confidence: 99%
“…(1) by setting n = 1. In order to obtain a calculated solvation free energy for S 8 which matched the measured solvation free energy Δ G sol exp ( S 8 ) = + 15.5 kJ / mol [ 11 ], it was necessary to increase the repulsive van der Waals parameter C 12 for atomic sulfur by a factor of 1.25, leading to a modified set of non-bonded LJ parameters σ = (1.25) 1/6 σ 0 and ε = (1.25) −1 ε 0 relative to the values ( σ 0 = 0.356359 nm , ε 0 = 1.04600 kJ / mol ) generated by ACPYPE. This yielded a calculated solvation free energy for S 8 of Δ G sol cal ( S 8 ) = − Δ G sol 1→0 ( S 8 ) = + 13.4 ± 1.4 kJ / mol .…”
Section: Systems and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slayer proteins (SLPs) are generally 40-200 kDa and represent up to 15% of total cellular protein production [4]. S-layers serve as the first selective barrier between the cell and its environment, which includes interactions with predators, symbionts, proteins, nutrients, and energy sources [5]. Bacterial S-layers have been linked to diverse functions, including protection from large macromolecules and predators, biofilm formation, adhesion, and pathogenesis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, it represents a first docking site for a number of extracellular molecules such as nutrients, vesicles, cells, and viruses 3,5 . Indeed, only recently, S-layer glycoproteins of hyperthermophilic archaea have been shown to accumulate iron and sulfur from the environment 27,28 . Also, recent studies revealed S-layer glycosylation to be crucial for cell-to-cell interactions during the mating process of the archaeon Haloferax 29 and comparative genomics suggest a within-niche variation of glycosylation enabling Haloferax to discriminate between such mating partners and also viruses 30 .…”
mentioning
confidence: 99%